2008
DOI: 10.1103/physreve.77.026303
|View full text |Cite
|
Sign up to set email alerts
|

Local and nonlocal strain rate fields and vorticity alignment in turbulent flows

Abstract: Local and nonlocal contributions to the total strain rate tensor Sij at any point x in a flow are formulated from an expansion of the vorticity field in a local spherical neighborhood of radius R centered on x. The resulting exact expression allows the nonlocal (background) strain rate tensor S B ij (x) to be obtained from Sij (x). In turbulent flows, where the vorticity naturally concentrates into relatively compact structures, this allows the local alignment of vorticity with the most extensional principal a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 22 publications
(76 reference statements)
11
55
1
Order By: Relevance
“…They take the same angular space at any location but the strengths and ration of the involved terms vary. It has been established that the strain rate tensor governs the dissipation of kinetic energy, the coupling of both, strain rate tensor and rotation rate tensor, governs the process of vortex stretching and vortex compression (Tsinober 2000;Hamlington et al 2008). For a better understanding of the vortex stretching and vortex compression mechanism, the coupling of the productions of strain and rotation are discussed with respect to the characteristic evolution of turbulence at different wall-normal locations in the TBL (figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…They take the same angular space at any location but the strengths and ration of the involved terms vary. It has been established that the strain rate tensor governs the dissipation of kinetic energy, the coupling of both, strain rate tensor and rotation rate tensor, governs the process of vortex stretching and vortex compression (Tsinober 2000;Hamlington et al 2008). For a better understanding of the vortex stretching and vortex compression mechanism, the coupling of the productions of strain and rotation are discussed with respect to the characteristic evolution of turbulence at different wall-normal locations in the TBL (figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Chakraborty 18 showed that the statistical behaviour of vorticity alignment with local principal strain rates can be significantly different for the corrugated flamelets regime of combustion with Le = 1.0, and for the thin reaction zones regime of combustion with non-unity Lewis number, in comparison to earlier studies. [8][9][10][11][19][20][21][22][23][24][25][26][27][28] For example, in the corrugated flamelets regime, and for the cases with high Karlovitz number and low Le, where the most extensive principal strain rate is controlled by the local dilatation rate, 18 the vorticity vector ⃗ ω predominantly aligns with the intermediate and the most compressive principal strain rates. Such an alignment of the vorticity vector differs from the alignment observed earlier in premixed 11 and non-premixed [8][9][10] flames with unity Lewis number, or in non-reacting flows.…”
Section: Introductionmentioning
confidence: 99%
“…Such an alignment of the vorticity vector differs from the alignment observed earlier in premixed 11 and non-premixed [8][9][10] flames with unity Lewis number, or in non-reacting flows. [19][20][21][22][23][24][25][26][27][28] While each individual species j has its own Lewis number Le j , in simplified models of molecular transport, the Lewis number of the deficient reactant (fuel or oxidant) is often taken to be the characteristic global Lewis number Le 29 as was done in the aforementioned analysis by Chakraborty. 18 It is worth noting here that alternative methods of assigning a characteristic Lewis number have been proposed based on heat release measurements 30,31 and mole fractions of the mixture constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Both ω and ∇φ are known to exhibit strong preferential orientation in the S ij eigenframe, with the vorticity vector aligning along the intermediate eigenvector S 2 [19,[21][22][23][24] [ Fig. 2(a)], and the scalar gradient vector aligning with the most compressive eigenvector S 3 [19] [ Fig.…”
Section: B Alignment Of ω and ∇φ In The Eigenframementioning
confidence: 99%